Exploring Anti-Inflammatory and Anti-Tyrosinase Potentials and Phytochemical Profiling of Cannabis sativa Stems Byproducts - Pannita Kongtananeti; Desy Liana; Hla Myo; Anuchit Phanumartwiwath; Chitlada Areesantichai (Sci)
Cannabis sativa L. has been traditionally used for its therapeutic properties, particularly in treating various skin conditions. This study explores the in vitro anti-aging potential of five distinct parts of C. sativa L. (inflorescence, seed, leaf, stem, and root) by analyzing their bioactive compounds and biological activities. Ultrasound-assisted extraction was employed using ethyl acetate as an extracting solvent, followed by chemical characterization via gas chromatography-mass spectrometry (GC-MS/MS) and liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QTOF-MS/MS) analyses. The biological assessment included antioxidant, anti-inflammatory, anti-tyrosinase activities, and cytotoxicity evaluations. The inflorescence extract demonstrated the antioxidant activity, with a half-maximal inhibitory concentration (IC50) value of 3,849.01 ± 5.25 µg/mL against DPPH radicals and 31.19 ± 0.96% inhibition of NO radicals at 1.25 mg/mL. Notably, the stem extract exhibited the highest anti-tyrosinase activity, with an IC50 value of 0.01 ± 0.00 mg/mL, and significantly inhibited 5-lipoxygenase (5-LOX) activity with an IC50 value of <0.024 µg/mL. All extracts showed no cytotoxicity on HaCaT cells at a concentration of 10 µg/mL, indicating their potential safety for dermatological applications. The stem extract was abundant in phytosterols, triterpenoids, diterpenoids, unsaturated fatty acids, and phenolic compounds, which likely contribute to its anti-inflammatory and anti-tyrosinase effects. These findings suggest that the stem, traditionally considered as waste, could be a valuable raw material for developing dermatological treatments with strong anti-inflammatory and skin-brightening effects.